2015
DOI: 10.1142/s0219686715500171
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of EDM Hole Drilling Parameters in Machining of MoSi2-SiC Intermetallic/Composites for Improving Geometrical Tolerances

Abstract: Intermetallic/ceramic composites with multiple responses are based on L18 orthogonal array with gray relational analysis (GRA). This paper presents a new approach for the optimization of drilling parameters on drilling MoSi 2– SiC composites. Optimal machining parameters can then be determined by the gray relational grade as the performance index. In this study, the sparking parameters namely current (I), pulse on time (t on ), pulse off time (t off ), spark gap and dielectric flushing pressure (P) are optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…In this investigation work, it is evident that all the results of the analysis discussed above are in line with those results reported in various literature. 6,1517,19,2326 The variation of entry hole diameter with servo feed rate and wire feed rate is illustrated in Figure 10. Similarly, the relationship of servo feed rate and T on time with exit diameter is depicted in Figure 11.…”
Section: Analysis and Interpretation Of Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this investigation work, it is evident that all the results of the analysis discussed above are in line with those results reported in various literature. 6,1517,19,2326 The variation of entry hole diameter with servo feed rate and wire feed rate is illustrated in Figure 10. Similarly, the relationship of servo feed rate and T on time with exit diameter is depicted in Figure 11.…”
Section: Analysis and Interpretation Of Experimental Resultsmentioning
confidence: 99%
“…These results have an overall strong concordance with the previous predictions. 6,15 The variation of hole circularity with servo feed rate and gap voltage is illustrated in Figure 13.
Figure 12.Influence of wire feed rate, T on , T off , gap voltage, and servo feed rate on hole circularity and taper.
Figure 13.Variation of hole circularity against servo feed rate and gap voltage.
…”
Section: Analysis and Interpretation Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drilling EDM works on the same principle as conventional EDM, but constantly rotating round hollow electrode and dielectric flushing through the electrode tube at high pressure (70-100 bar) are the main distinct features between fast hole drilling EDM and other EDM methods. In addition, it is utilized in many industrial applications such as to create cooling holes in turbine blades, injection nozzles, cutting tool coolant holes, plastic mould vent holes and starter holes in wire EDM [14][15][16][17][18]. It is also found that increasing MRR with desired geometry and good dimensional quality is difficult to accomplish during machinability of harder materials [19].…”
Section: Introductionmentioning
confidence: 99%
“…Carr and Ferreira 15 formulated straightness,°atness and cylindricity as the nonlinear problems, which were then changed into a series of linear problems. Selvarajan et al 16 present a new approach using gray relational analysis for optimization of EDM parameters to get improved circularity and cylindricity. Islam and Pramanik 17 investigated the e®ect of turning parameters on improving the circularity of parts.…”
Section: Introductionmentioning
confidence: 99%